T follicular helper cell biology: A decade of discovery and diseases - Crotty, Shane (Immunity, 2019)
Helping B cells and antibody responses is a major function of CD4(+) T cells. It has been 10 years since the publication of Bcl6 as the lineage defining transcription factor for T follicular helper (Tfh) differentiation and the requirement of Tfh cells as the specialized subset of CD4(+) T cells needed for germinal centers (the microanatomical sites of B cell mutation and antibody affinity maturation) and related B cell responses. A great deal has been learned about Tfh cells in the past 10 years, particularly regarding their roles in a surprising range of diseases. Advances in the understanding of Tfh cells differentiation and function are discussed, as are the understanding of Tfh cells in infectious diseases, vaccines, autoimmune diseases, allergies, atherosclerosis, organ transplants, and cancer. This includes discussion of Tfh cells in the human immune system. Based on the discoveries to date, the next decade of Tfh research surely holds many more surprises.